Devising an energy pricing strategy for GCC countries - Bacon, R (Oxford Institute for Energy Studies, 2014)
All the GCC states provide their domestic economies with energy at a fraction of the international price, using both direct and indirect subsidies. Although such subsidies reflect important economic and social goals, they also impose large costs on their economies. The increasing scale of such subsidies is becoming harder to justify and a strategy for their reform will become ever more pressing.